Phosphorus and Potash Availability in the Salt Affected Soil of Bhal Region (Gujarat) asÂ· Influenced by Natural Drying, Levels of Phosphorus Sources and FYM - Patel, V S; Patel, J C (Annals of Arid Zone, 2016)
Incubation of a 'Bhal' soil with or without farin yard manure (FYM) and phosphorus from different sources showed that application of FYM markedly decreased the soil pH and significantly enhanced the P and K availability in the soil. The P and K availability of soil reduced significantly when moisture was depleted from 40 to 10%. Again on rewetting the soil, nutrients availability was restored. Application of diammonium phosphate significantly increased the Olsen's P in the soil as compared to that with monocalcium phosphate.